Implementation of corporate governance (cg) by creating corporate culture: A case study in Religion Ministry Of Kediri district, East Java, Indonesia. - Wahyu Puspitasari, Ajeng (Universiti Sains Malaysia, 2014)
Observing the reality, there is quite a lot of corporation or even Ministry in Indonesia that have not been implemented Corporate Governance (CG) properly. It encourage to conduct studies within research was aimed to analyze the employer’s respond and the effect of implementation of Tahajjud as a corporate culture in Religion Ministry of Kediri District.